2004
DOI: 10.1080/09583150310001655710
|View full text |Cite
|
Sign up to set email alerts
|

Bioherbicidal effect of fumonisin B1, a phytotoxic metabolite naturally produced byFusarium nygamai, on parasitic weeds of the genusStriga

Abstract: Fusarium nygamai has been isolated and identified from diseased Striga hermonthica plants collected from sorghum fields in the Sudan. Fumonisin B 1 , produced by this fungus, was isolated and purified. In in vitro experiments, the bioherbicidal potential of this mycotoxin was evaluated against S. hermonthica and S. asiatica. Different concentrations (250, 500 and 1000 mg L (1 of water) of fumonisin B 1 , applied during the conditioning phase of the Striga seeds significantly reduced the germination of both spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…(Gilchrist 1997;Stone et al 2000;Kroschel and Elzein 2004). FB1 is a sphinganine-analog mycotoxin (SAM) which inhibits ceramide synthase activity and therefore induces disruption of sphingolipid metabolism leading to cell death (Wang et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…(Gilchrist 1997;Stone et al 2000;Kroschel and Elzein 2004). FB1 is a sphinganine-analog mycotoxin (SAM) which inhibits ceramide synthase activity and therefore induces disruption of sphingolipid metabolism leading to cell death (Wang et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…, ), ascaulitoxin, aglycone and trans‐4‐aminoproline, which were isolated and characterized from the culture filtrate of Ascochyta caulina (Amusa ), fumonisin B1 from Fusarium moniliforme and Fusarium nygamai (Abbas et al . ; Krosche and Elzein ), fusaric acid, 10‐11‐dehydrofusaric acid and their methyl esters from Fusarium oxysporum (Savard et al . ; Amalfitano et al .…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, microbial phytotoxins and/or their synthetic analogues could be considered as sources of such useful herbicides (Evidente and Abouzeid 2006;Rimando and Duke 2006). There are several phytotoxins which have been commercialized, such as phosphinothricin (glufosinate), bialaphos, hydantocidin (Saxena and Pandey 2001;Pandey et al 2003Pandey et al , 2004, ascaulitoxin, aglycone and trans-4-aminoproline, which were isolated and characterized from the culture filtrate of Ascochyta caulina (Amusa 2006), fumonisin B1 from Fusarium moniliforme and Fusarium nygamai (Abbas et al 1991;Krosche and Elzein 2003), fusaric acid, 10-11-dehydrofusaric acid and their methyl esters from Fusarium oxysporum (Savard et al 1997;Amalfitano et al 2002), and AAL toxin from Alternaria alternata (Abbas et al 1995;Mesbah et al 2000). The aim of this study was to find a fungal pathogen specific to C. arvensis for the production of secondary product(s).…”
Section: Introductionmentioning
confidence: 99%
“…Formulations can extend the period of time before dew is required, and adjuvants such as unrefined corn oil and Silwet L-77 can improve chances for success of mycoherbicides (Abbas et al, 2004;Boyette, 2006;Boyette et al, 2007a). Elzein et al (2004) found that Fusarium oxysporum 'Foxy 2' could be encapsulated in a pesta formulation to improve shelf life. Amsellem et al (1999) utilized the 'Stabileze' formulation (containing starch, sucrose, corn oil and silica) to enhance preservation of mycelia from two Fusarium spp.…”
Section: Formulations To Improve Success Of Microbial Herbicidesmentioning
confidence: 99%
“…poae isolate JT-P482) was registered in Japan for control of annual bluegrass (Poa annua L.) in 1997 (Imaizumi et al, 1999 The mode of action of each biocontrol agent is as varied as the microorganisms themselves (de Luna et al, 2011). They range from simple but effective compounds like cyanide (Kremer & Souissi, 2001;Owen & Zdor, 2001) and organic acids to complex molecules with tertiary structure (Bouizgarne et al, 2006;Gurusiddaiah et al, 1994), and from secondary metabolites (Kroschel & Elzein, 2004) to plant growth regulators, such as auxins and ethylene (de Luna et al, 2005). Pedras et al (2003) isolated toxins from Pseudomonas fluorescens strain BRG100.…”
Section: Successful Microbial Herbicidesmentioning
confidence: 99%